Model Joint Economic Lot Size (JELS) pada Kasus Pemanufaktur-Pembeli dengan Permintaan Probabilistik dan Lead Time Variabel - Wakhid Ahmad Jauhari (Industrial Engineering Study Program, Faculty of Engineering, Universitas Sebelas Maret, 2008)
We consider a two-layer supply chain model consisting of a vendor and a buyer. The buyer observes a probabilistic demand and orders lots from the vendor. We relax the assumption of deterministic lead time and assume that it is varying linearly with the delivery lot size. The vendor manufactures the requested product in production batchs. Each produced batch is shipped to the buyer in lots. We consider a situation where there are multiple deliveries for one order and the vendor produces in a multiple integer of delivery quantity and hence, an order can be split into a number of production runs. A solution procedure is suggested for solving the proposed model and numerical examples are used to illustrate the benefit of integration. Numerical results show that the integrated inventory model will always result in savings in the total joint cost, buyer cost and vendor cost.